Robust Bioinspired Graphene Film via pi-pi Cross-linking - Ni,H; Xu,F; Tomsia,AP; Saiz,E; Jiang,L; Cheng,Q (ACS APPLIED MATERIALS & INTERFACES, 2017)
Graphene composite films inspired by nacre are the subject of ongoing research efforts to optimize their properties for applications in flexible energy devices. Noncovalent interactions do not cause interruption of the delocalized conjugated π-electron system, thus preserving graphene’s excellent properties. Herein, we synthesized a conjugated molecule with pyrene groups on both ends of a long linear chain (AP-DSS) from 1-aminopyrene (AP) and disuccinimidyl suberate (DSS). The AP-DSS molecules are used to cross-link adjacent graphene nanosheets via π–π interfacial interactions to improve properties of graphene films. The tensile strength and toughness of resultant graphene films were 4.1 and 6.4 times higher, respectively, than that of pure rGO film. More remarkably, the electrical conductivity showed a simultaneous improvement, which is rare to be achieved in other kinds of covalent or noncovalent functionalization. Such integration demonstrates the advantage of this work to previously reported noncovalent functionalization of graphene.